FEATURES OF LAPAROSCOPIC FUNDOPLICATION FOR HIATAL HERNIA IN PATIENTS WITH HIGH BODY MASS INDEX - Khakimov , M.Sh.; Berkinov , U.B.; Sattarov , O.T.; Ermatov , B.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The results of examination and surgical treatment of 22 patients who underwent laparoscopic Nissen-Rosetti fundoplication were analyzed. Depending on the constitutional features and body mass index, the authors proposed methods for introducing trocars and developed a computer program. The proposed software facilitates the determination of the most convenient points for the introduction of trocars, which makes it easy to manipulate the instrument without requiring their rearrangement, and thereby improves the clinical results of surgical interventions.